2023
DOI: 10.1002/leg3.190
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hermetic bags with polyethylene‐lined polypropylene bags for prolonged storage of faba bean (Vicia faba L.) seeds in Ethiopia

Abstract: Poor storage facilities expose seeds to deterioration, resulting in low seed quality under a prolonged storage time. We compared the performance of five bag types: Two hermetic bags (Super GrainPro bag [SGB] and Purdue Improved Crop Storage bag [PICS]), with three non‐hermetic bags (woven polypropylene bag lined with polyethylene [WPP lined with PE], polypropylene bags [PP], and jute bags) for the storage of faba bean seeds for 24 months. Faba bean seed quality was assessed under ambient conditions after 0, 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The practice of reusing the inner lining of fertilizer-woven polypropylene with a single HDPE polyethylene bag for crop storage is also common in Ethiopia. For instance, Seifu et al [ 34 ] reported that the efficacy of the non-hermetic fertilizer bag (woven polypropylene bag lined with single layer polyethylene) is better compared to hermetic bags compared to polypropylene bags and jute bags that are not hermetic for 12 months of storage duration on the quality of faba bean seeds in ambient storage. Furthermore, Damte and Tiruaynet [ 35 ] reported that the higher the efficacy of hermetic storage packaging materials such as the Grain Prosuper bag, Purdue's Improved Crop Storage (PICS) bag and fertilizer bag than the polypropylene bag during storage of tef, durum wheat, lentil, and chickpea seeds for 24 months.…”
Section: Introductionmentioning
confidence: 99%
“…The practice of reusing the inner lining of fertilizer-woven polypropylene with a single HDPE polyethylene bag for crop storage is also common in Ethiopia. For instance, Seifu et al [ 34 ] reported that the efficacy of the non-hermetic fertilizer bag (woven polypropylene bag lined with single layer polyethylene) is better compared to hermetic bags compared to polypropylene bags and jute bags that are not hermetic for 12 months of storage duration on the quality of faba bean seeds in ambient storage. Furthermore, Damte and Tiruaynet [ 35 ] reported that the higher the efficacy of hermetic storage packaging materials such as the Grain Prosuper bag, Purdue's Improved Crop Storage (PICS) bag and fertilizer bag than the polypropylene bag during storage of tef, durum wheat, lentil, and chickpea seeds for 24 months.…”
Section: Introductionmentioning
confidence: 99%